2022
DOI: 10.3389/fpls.2022.857896
|View full text |Cite
|
Sign up to set email alerts
|

The Next Generation of Rice: Inter-Subspecific Indica-Japonica Hybrid Rice

Abstract: Rice (Oryza sativa) is an important food crop and has two subspecies, indica and japonica. Since the last century, four generations of rice varieties have been applied to rice production. Semi-dwarf rice, intra-subspecific hybrid rice, and inter-subspecific introgression rice were developed successively by genetic modification based on the first generation of tall rice. Each generation of rice has greater yield potential than the previous generation. Due to the stronger heterosis of indica-japonica hybrids, ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…In the past decades, great progress has been made in the heterosis utilization of hybrid rice (Yuan, 2017 ; Zhang, 2022 ). Improving the outcrossing ability of MSLs is very important for hybrid rice seed production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, great progress has been made in the heterosis utilization of hybrid rice (Yuan, 2017 ; Zhang, 2022 ). Improving the outcrossing ability of MSLs is very important for hybrid rice seed production.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, hybrid rice has been widely planted in China and around the world (Yuan and Virmani, 1988 ). The hybrid rice exhibits strong heterosis, which plays an important role in improving rice yield (Cheng et al, 2007 ; Zhang et al, 2021 ; Zhang, 2022 ). Since male sterility lines (MSLs) are used to produce hybrid seeds by outcrossing with restorer lines of male parents, the outcrossing ability of MSLs is a key factor in improving hybrid seed yield.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of heterosis is still unclear through extensive studies on genome, transcriptome and epigenetics ( Larièpe et al, 2012 ; Shen et al, 2014 ; Shao et al, 2019 ; Wang and Wang, 2022 ; Zhang, 2022 ). In recent years, several ncRNAs and their corresponding regulatory networks have been proved to play important roles in plant growth and development ( Ohtani, 2017 ; Yuan et al, 2018 ; Luan et al, 2019 ; Wang et al, 2020 ; Zhai et al, 2020 ; Chand Jha et al, 2021 ; Qiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few studies on the role of ncRNA in plant heterosis so far, which have been conducted in maize and cabbage ( Crisp et al, 2020 ; Hou et al, 2020 ; Li et al, 2021 ). As a hybrid rice with high yield potential, indica × japonica hybrid rice has always been an important material for heterosis research ( Xiong et al, 2021 ; Zhang, 2022 ). This study demonstrated that ncRNA plays an important role in the heterosis of inter-subspecific hybrid rice by comprehensively analyzing the expression profile of ncRNA and the ncRNA regulatory network related to heterosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation